THE EFFECT OF FEEDING MULBERRY HYBRID ON THE PRODUCTIVITY AND THE QUALITY OF COCOON SILKWORM - Sugeng Pudjiono; Mohamad Na'iem (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
Hybridization Morus sp, has given a significant impact increasing leaf productivity. There ore some good performaning Morus hybrids such as M. nigra x M. indica (M.N1). M. australis x M. indica (M.AsI). and M. alba var kanva which might be good forfeeding materials of silkworm. However, it is necessariy to test the leafsuitability asfeeding material to the quality of cocoon that will be produced. For that purpose one set offeeding experimentation using Bombyx mori L, (bivoltine silkworm egg F1 China and Japan double crossed with the code C 301) and three kinds of mulberry was established. The researeh located in Grogolan village, with 500 m asl. altitude, 2.500 mm - 3.000 mm rain per year, 75% relative humidity and 25° .3,0°C temperature. The study was arranged Randomized Completely Design with three replications. The result showed that the effects of mulberry leaves were non signifcant for the survival percentage of silkvorm instar I-III, the survival percentage of silkworm instar IV-V, weight of cocoon, weight of cocoon shell, cocoon shell percentage, length of filament, weight of filament, filament percentage and reelability of cocoon, There were significant differences in rendement ofrearing. In general, leaves those three hybrids are suitable for silkwonn feeding.